“Taak prappa” - Kathie Birat (Sillages Critiques)
David Dabydeen’s collection of poems Slave Song (1984) represents the Guyanese poet’s attempt to compensate for the silence surrounding slavery and the absence of a significant body of poetry in Creole. In a series of 14 poems written in Guyanese Creole and accompanied by illustrations dating from the eighteenth and nineteenth centuries as well as explanatory notes and translations in standard English, the poet evokes the lives of plantation slaves and modern-day peasants through forms that both imitate folk poetry and evoke European genres like the pastoral and the elegy. Through an analysis of this intertwining of local and European forms and of the use of Creole in Slave Song, this article examines the collection as an attempt on the part of the poet both to generate presence and to recognize the impossibility of filling the gaps left by a painful past.